Fat Grafting into Younger Recipients Improves Volume Retention in an Animal Model. Issue 4 (April 2019) - Chung, Natalie N.; Ransom, Ryan C.; Blackshear, Charles P.; Irizarry, Dre M.; Yen, Derek; Momeni, Arash; Lee, Gordon K.; Nguyen, Dung H.; Longaker, Michael T.; Wan, Derrick C.
Abstract : Background: Soft-tissue deficits associated with various craniofacial anomalies can be addressed by fat grafting, although outcomes remain unpredictable. Furthermore, consensus does not exist for timing of these procedures. Whereas some advocate approaching soft-tissue reconstruction after the underlying skeletal foundation has been corrected, other studies have suggested that earlier grafting may exploit a younger recipient niche that is more conducive to fat graft survival. As there is a dearth of research investigating effects of recipient age on fat graft volume retention, this study compared the effectiveness of fat grafting in younger versus older animals through a longitudinal, in vivo analysis. Methods: Human lipoaspirate from three healthy female donors was grafted subcutaneously over the calvaria of immunocompromised mice. Volume retention over 8 weeks was evaluated using micro–computed tomography at three experimental ages: 3 weeks, 6 months, and 1 year. Histologic examination was performed on explanted grafts to evaluate graft health and vascularity. Recipient-site vascularity was also evaluated by confocal microscopy. Results: The greatest retention of fat graft volume was noted in the youngest group compared with both older groups ( p < 0.05) at 6 and 8 weeks after grafting. Histologic and immunohistochemical analyses revealed that improved retention in younger groups was associated with greater fat graft integrity and more robust vascularization. Conclusion: The authors' study provides evidence that grafting fat into a younger recipient site correlates with improved volume retention over time, suggesting that beginning soft-tissue reconstruction with fat grafting in patients at an earlier age may be preferable to late correction. Abstract : Supplemental Digital Content is available in the text.